(untitled) (Costa Rican Journal of Guidance & Counseling, 2022)
This article analyzes the undelayable need to define a guiding action from a group perspective in preschool education. It reflects on the importance of early childhood education, which has been considered by international organizations and the government as a critical stage. Therefore, it should be deemed as such by the Guidance Service. Some arguments are presented to outline guiding intervention under a group modality, adjusted to the purposes, the nature of the work, and the characteristics of preschool education.